2015
DOI: 10.1245/s10434-015-4441-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival is Better After Breast Conserving Therapy than Mastectomy for Early Stage Breast Cancer: A Registry-Based Follow-up Study of Norwegian Women Primary Operated Between 1998 and 2008

Abstract: BackgroundBreast-conserving therapy (BCT) and mastectomy (MTX) has been considered to have a similar long-time survival. However, better survival in women undergoing BCT compared with MTX is found in two recent register studies from the United States. The purpose of this study was to compare survival after BCT and MTX for women with early-stage breast cancer in Norway.MethodsWomen with invasive, early-stage breast cancer (1998–2008) where BCT and MTX were considered as equally beneficial treatments were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 17 publications
8
86
0
5
Order By: Relevance
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
“…Large randomized controlled trials (RCTs) in the 1980s have shown equal survival for breast‐conserving therapy (breast‐conserving surgery plus radiation therapy, BCT) and mastectomy in early stage breast cancer . Over recent years, however, multiple observational studies have challenged this equivalence, showing superior survival for patients treated with BCT compared to those treated with mastectomy . The use of population‐based observational studies in studying treatment effects can be of additional value on outcomes obtained through RCTs.…”
mentioning
confidence: 99%
“…Compared with patients who have breast-conserving therapy, patients with early-stage cancer who have mastectomies have longer delays to adjuvant chemotherapy and radiation and lower rates of BCSS [36,37]. In contrast, rates of discontinuation of endocrine therapy were similar to national cohorts; 50% of patients nationally, and 48% in our sample, with schizophrenia with estrogen receptor/progesterone receptor-positive breast cancer had discontinued endocrine therapy at 5 years [38,39].…”
Section: Discussionmentioning
confidence: 60%
“…Previous authors indicated long‐term overall survival rates between 77% and 94% in patients underwent BCS followed by standard radiotherapy with or without boost . Despite the high ipsilateral breast cancer recurrence found in our study, the 10‐year overall survival of 82.8% was in accordance with previous literature.…”
Section: Discussionmentioning
confidence: 99%